A cascading-response fluorescent probe for real-time pH monitoring during cysteine-depletion process in pancreatic cancer cells - Qin, Xue; Zhang, Shuping; Guo, Xiaolu; Liu, Xingyue; Shen, Xing-Can (Frontiers in Bioengineering and Biotechnology, 2022)
Pancreatic cancer (PC) is one of the deadliest human malignancies and exploring the complex molecular mechanism behind cell death will greatly promote the clinical treatment of PC. Here, we report a cascading-response fluorescent imaging probe, Cy-Cys-pH, for the sequential detection of cysteine (Cys) and pH in pancreatic cancer cells. In the presence of Cys, Cys-mediated cleavage of acrylate group makes Cy-Cys-pH to be transformed into Cy-Cys-O, which induces intense fluorescence enhancement at 725 nm. Then, Cy-Cys-O is protonated to obtain Cy-Cys-OH and the fluorescence emission shifted to 682 nm showing ratiometric pH response. Furthermore, using Cy-Cys-pH, we monitored the intracellular pH during the therapeutic process with anticancer drugs and evaluated the ability of three anticancer drugs to kill Panc-1 cells, demonstrating that associating Cys and pH is in part an effective anticancer strategy in the treatment of pancreatic cancer. Significantly, Cy-Cys-pH is able to real-time monitor and image pH changes during Cys depletion which further revealing the molecular mechanism of Cys-depleted pancreatic cancer cell death providing a powerful molecular tool for the precise treatment of PC.